Government Policies in the Preservation of Malay Culture in Siak Regency, Riau - Dessy Artina (Faculty of Law, Jambi University, 2021)
This article discusses the local government policies with respect to Malay culture in Siak, one of the regencies in Riau Province. It is based on the fact that Malay culture is inseparable part of Siak. Historically speaking, Malay culture has been there since the early formation of the Siak Kingdom in 1723 AD. Having and promoting itself with a slogan “The Truly Malay,” Siak is proud of standing upon Malay culture. The reflection of Malay culture as well as its traditions is established in day-to-day lives witnessed in its language and clothing. Aiming at preserving the culture, the local government has made a policy in the form of Regional Regulations on Malay Language and Culture. However, as will be demonstrated through a normative approach, the implementation of the Regional Regulation is still constrained due to the absence of a Regent Regulation which is hoped to function as an implementing regulation. Addressing such a problem has to be integrated into various policies in the form of a District Head Regulation.